Effectiveness of Animaker-Based Animated Video Development Using the ADDIE Model on Elementary Students’ Mathematics Learning Outcomes - Akmal Rijal; Dodik Mulyono (Universitas Pendidikan Ganesha, 2026)
Students frequently view mathematics as being challenging at the elementary school level due to its abstract character and the sparse use of interactive teaching techniques. The quick advancement of digital technology, especially animation, presents chances to create learning materials that are more interesting and easy to understand. The purpose of this project was to explore effectiveness of animaker-based animated video development using the addie model on elementary students’ mathematics learning outcomes. The five stages of the ADDIE framework Analysis, Design, Development, Implementation, and Evaluation were adhered to during the development process. Forty-five fifth-grade students and one instructor participated in the field trial. Learning accomplishment tests pretest and posttest were used to gather quantitative data, which were then analyzed using the N-Gain score. Teachers' and students' responses through questionnaires and interviews provided qualitative data, which was then analyzed descriptively. With an N-Gain score of 0.74 in the high category, the study results indicate that the media developed has a very high validity of 92%, excellent practicality of 90%, and high effectiveness. Responses from teachers and students were overwhelmingly positive, especially when it came to the visual quality, engagement, and use. In summary, Animaker-based animated movies are practical and successful as cutting edge resources for math instruction in elementary schools, highlighting the significance of incorporating animation technology to improve student accomplishment and learning quality.